Attitude 101 : What Every Leader Needs to Know - Maxwell, John C., 1947- (Nashville Thomas Nelson, 2003)
Popular leadership speaker John C. Maxwell incorporates all his best teachings into this easy-to-read primer for developing the right attitude
Include Notes
Keywords: Success--Psychological aspects -- Attitude (Psychology)